Halomonas lactosivorans sp. nov., isolated from salt-lake sediment. Issue 5 (14th May 2020) - Ming, Hong; Ji, Wei-li; Li, Meng; Zhao, Zhuo-li; Cheng, Li-jiao; Niu, Ming-ming; Zhang, Ling-yu; Wang, Yan; Nie, Guo-xing
Abstract : A bacteria strain, designated CFH 90008 T, was isolated from a salt lake sediment sample collected from Yuncheng city, Shanxi Province, PR China. Strain CFH 90008 T was Gram-stain-negative, strictly aerobic, motile with lateral flagella and rod-shaped. Colonies were yellow, circular and smooth. Phylogenetic analyses based on 16S rRNA gene sequences indicated that strain CFH 90008 T belonged to the genus Halomonas, showing highest sequence similarity to Halomonas daqingensis DQD2-30 T (98.6 %), Halomonas saliphila LCB169 T (98.5 %), Halomonas desiderata FB2 T (98.1 %) and Halomonas kenyensis AIR-2 T (98.0 %). Good growth was observed at 10–50 °C, pH 6.0–9.0 and with NaCl concentration from 1.0 to 12.0 % (w/v). The predominant quinone was Q9. The major fatty acid (>10 %) was C18 : 1 ω7 c, C16 : 0 and C16 : 1 ω7 c . The genome of strain CFH 90008 T was 4.36 Mbp with a genomic DNA G+C content of 66.7 mol%. Based on low average nucleotide identity and DNA–DNAhybridization results, chemotaxonomic characteristics, and differential physiological properties, strain CFH 90008 T could not be classified into any recognized species of the genus Halomonas . Therefore, a new species, for which the name Halomonas lactosivorans sp. nov. is proposed. The type strain is CFH 90008 T (=DSM 103220 T =KCTC 52281 T ).